МОДЕРНИЗАЦИЯ КИТАЯ С ТРАДИЦИОННОЙ ДАНЬЮ К ПРОШЛОМУ - Каскарауова, А.; Бектурганова, П. (Journal of Oriental Studies, 2016)
Мақалада Қытай өркениетінiң қазiргi даму кезеңін-дегі идеологиясы және жаңғырту үдерістерінде Қытайелінің көне дәстүрлерінің ықпалы қарастырылады.This article examines the ideological line of the currentleadership, which is caused by a combination of modernculture and the finest achievements of traditional Chineseculture. Analyze the influence of the ancient traditions ofChina's current model of China's modernization.